The Effects of Intention and Risk Awareness on Household Waste Management Behavior During Covid-19 Outbreak - Kirana Rukmayuninda Ririh; Luthfina Ariyani (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
Coronavirus Disease 2019 (Covid-19) Pandemic had been hitting throughout the world since early 2020. Indonesia faces severe impacts, including the deaths of millions of people and vast virus transmission through a bad waste management system. Since the government applied lockdown in many regions, household waste increases and led to various problems. This research aims to explain household waste management intention during Covid-19, especially in a metropolitan city like Jakarta. This research adopts the Theory of Planned Behavior and examines the impacts of pandemic awareness, knowledge, and religion. Participants were involved in this study are 314 respondents. Questionnaires were gathered through emails, messenger applications, and social media. We use Structural Equation Modelling, particularly Confirmatory Factor Analysis, to analyze data and utilize LISREL 8.80. Results show that household waste management behavior can be encouraged through intention and pandemic risk awareness. Meanwhile, perceived behavioral control and household expenditures have to impact to intention to manage household waste. Moreover, government support also plays an important role in enhancing the intention of managing household waste. Therefore, social media and religious activities can be used to raise the level of risk awareness.